1999
DOI: 10.1046/j.1440-1738.1999.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical contrast between the Sanbagawa psammitic schists (Oboke unit) and the Cretaceous Shimanto sandstones in Shikoku, Southwest Japan and its geologic significance

Abstract: A systematic geochemical study of sandstones from the Cretaceous Shimanto Supergroup and psammitic schists from the Oboke unit in Shikoku has been carried out in order to clarify the depositional age of the protoliths of the Oboke psammitic schists. The geochemical data, together with chronological and geologic data, led to the following conclusions. (i) It is inferred that Oboke psammitic schists are metamorphically equivalent to sandstones in the Hiwasa Formation of the Shimanto accretionary complex, deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Isozaki, 1986;Isozaki and Maruyama, 1991). This relationship was initially suggested by Shinjoe and Tagami (1994), Manabe et al (1996) and Kiminami et al (1999), and has been confirmed by recent U-Pb geochronology of detrital zircons separated from metamorphic rocks (Aoki et al, 2007) and deep seismic profile data (Sato et al, 2005;Ito et al, 2009). Furthermore, Aoki et al (2008) demonstrated that these rocks underwent blueschist-facies metamorphism (sensu lato) at 66-61 Ma, much younger than the ages of peak metamorphism of Sanbagawa metamorphic rocks.…”
Section: Shikokumentioning
confidence: 53%
See 1 more Smart Citation
“…Isozaki, 1986;Isozaki and Maruyama, 1991). This relationship was initially suggested by Shinjoe and Tagami (1994), Manabe et al (1996) and Kiminami et al (1999), and has been confirmed by recent U-Pb geochronology of detrital zircons separated from metamorphic rocks (Aoki et al, 2007) and deep seismic profile data (Sato et al, 2005;Ito et al, 2009). Furthermore, Aoki et al (2008) demonstrated that these rocks underwent blueschist-facies metamorphism (sensu lato) at 66-61 Ma, much younger than the ages of peak metamorphism of Sanbagawa metamorphic rocks.…”
Section: Shikokumentioning
confidence: 53%
“…The Northern Shimanto belt is defined as an accretionary complex formed during the Upper Cretaceous (e.g. Taira et al, 1982;Kiminami et al, 1998Kiminami et al, , 1999.…”
Section: Shikokumentioning
confidence: 99%
“…These belts could not be distinguished prior to the advent of single zircon dating due to similar lithologies and metamorphic grade, though Kiminami et al (1999), Kiminami and Ishihama (2003), and Kiminami (2010) already recognized similarities in the geochemical composition of metasediments now considered to constitute the Shimanto Metamorphic Rocks and sediments of the nonmetamorphic Shimanto Belt.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some authors have already argued that the Koboke and Kawaguchi Formations may represent underplated deeper facies of the Cretaceous Shimanto accretionary complex e.g. Isozaki and Maruyama, 1991;Kiminami et al, 1999 . To solve the debate, it is critical to find out microfossil or to get high-resolution age determination of zircon to document the depositional age constraints. However, nobody has succeeded to report any occurrence of microfossils in the Oboke area because of extensive ductile deformation.…”
mentioning
confidence: 99%